Acral rash in a child with COVID-19. - Mazzotta, F.; Troccoli, T.; Caselli, D.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
A 9-year-old boy suffering from COVID-19 presented after an acute conjunctivitis, symptomatic glossitis, cheilitis, then reticular livedo, urticaria angioedema and finally a palmar-plantar scarlet fever-like rash. These COVID-19 symptoms observed consecutively in the same child have been described in isolation among the cutaneous manifestations of COVID-19. The authors discuss the pathogenesis of these late symptoms of SARS-CoV-2 infection.